Perception and Practice of Online Learning among Nursing Students in Dhanusha, Nepal - Thapa, Safee; Rijal, Mala; Chaudhary, Tanuja Kumari (Janaki Medical College Journal of Medical Science, 2023)
Background & Objective: With the increasing use of technology in education, online learning has become a common teaching methods. The objective of the study was to find out perception and practice of online learning among nursing students Dhanusha, Nepal.Material and Methods: The descriptive cross-sectional research design was used to find out perception and practice of online learning among nursing students in Dhanusha, Nepal. Students studying in academic program of Proficiency Certificate Level, Generic Bachelor Science Nursing, and Bachelor in Nursing Science were identified from seven conveniently selected nursing colleges out of the nine nursing college in the study area. Simple Random sampling technique (Lottery Method) was used to selected students from selected nursing colleges. A total 392 nursing students participated in this study, and all students filled out the questionnaire completely. Data entry and analysis were done in Statistical Package for Social Science (SPSS) version 17. The collected data were analyzed using descriptive statistical methods like frequency, percentage, mean, and inferential statistics chi -square test was applied to measure associations between level of perception and practice with selected variables.Results: The descriptive cross-sectional research design was used to find out perception and practice of online learning among nursing students in Dhanusha, Nepal. Students studying in academic program of Proficiency Certificate Level, Generic Bachelor Science Nursing, and Bachelor in Nursing Science were identified from seven conveniently selected nursing colleges out of the nine nursing college in the study area. Simple Random sampling technique (Lottery Method) was used to selected students from selected nursing colleges. A total 392 nursing students participated in this study, and all students filled out the questionnaire completely. Data entry and analysis were done in Statistical Package for Social Science (SPSS) version 17. The collected data were analyzed using descriptive statistical methods like frequency, percentage, mean, and inferential statistics chi -square test was applied to measure associations between level of perception and practice with selected variables.Conclusion: The findings showed that 52.55% had favorable perceptions towards online learning, which was comparatively higher than unfavorable perceptions, which were 47.35%. Among the 392 respondents, 16 (4.08%) had not attended an online class. Among 377 respondents who had taken online classes, 248 (63.27%) had good practice while the practice of 128 (32.6%) was found to be poor. There was a statistically significant association between perception and practice. Similarly, there was an association between perception and the academic year of a nursing student, as well as between perception and monthly family income.